ANALYTICAL PERFORMANCE OF PROCALCITONIN LEVEL BETWEEN CHEMILUMINESCENCE AND QUANTITATIVE IMMUNOCHROMATOGRAPHY METHODS IN SEPSIS PATIENTS - Mario Mario; Betty Agustina Tambunan; Hardiono Hardiono (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Sepsis is a public health problem in many countries. The latest diagnosis criteria are quick Sequential Organ Failure Assessment (qSOFA). Procalcitonin (PCT) could be used to aid the diagnosis of sepsis. The aim of this study was to determine the diagnostic value of PCT between CLIA and quantitative immunochromatography tests in sepsis patients. Samples were obtained from the resuscitation room, intensive observation room, and Intensive Care Unit (ICU) Dr. Soetomo General Hospital between December 2017-February 2018. One hundred and one subjects were examined and classified into sepsis group (n=71) and healthy group (n=30), based on qSOFA and SIRS criteria. Procalcitonin test with CLIA and quantitative immunochromatography method were performed in all subjects, followed by culture examination in sepsis group using PhoenixTM 100. The diagnostic value of the two methods was analyzed by 2x2 table with a Confidence Interval (CI) of 95%. There were significant differences of procalcitonin level between CLIA and quantitative immunochromatography method in the sepsis group (p=0.009) and in the healthy group (p=0.002). The diagnostic value of procalcitonin level by CLIA method with a cut-off value ≥ 0.27 ng/mL (AUC=0.839, sensitivity (Sn)=74.6%, specificity (Sp)=86.7%, Positive Predictive Value (PPV)=93%, Negative Predictive Value (NPV)=59.1%) had the same sensitivity but higher specificity, PPV, and NPV rather than by quantitative immunochromatography method (AUC=0.786, Sn=74.6%, Sp=66.7%, PPV=84.1%, NPV=52.6%). Procalcitonin examination with CLIA had a better diagnostic value than quantitative immuno-chromatography method.